Cold-Setting Inkjet Printed Titania Patterns Reinforced by Organosilicate Binder - Králová, Marcela; Dzik, Petr; Kašpárek, Vít; Veselý, Michal; Cihlář, Jaroslav (Molecules (Basel, Switzerland), 2015)
A hybrid organo-silica sol was used as a binder for reinforcing of commercial titanium dioxide nanoparticles (Evonic P25) deposited on glass substrates. The organo-silica binder was prepared by the sol-gel process and mixtures of titania nanoparticles with the binder in various ratios were deposited by materials printing technique. Patterns with both positive and negative features down to 100 µm size and variable thickness were reliably printed by Fujifilm Dimatix inkjet printer. All prepared films well adhered onto substrates, however further post-printing treatment proved to be necessary in order to improve their reactivity. The influence of UV radiation as well as of thermal sintering on the final electrochemical and photocatalytic properties was investigated. A mixture containing 63 wt % of titania delivered a balanced compromise of mechanical stability, generated photocurrent density and photocatalytic activity. Although the heat treated samples yielded generally higher photocurrent, higher photocatalytic activity towards model aqueous pollutant was observed in the case of UV cured samples because of their superhydrophilic properties. While heat sintering remains the superior processing method for inorganic substrates, UV-curing provides a sound treatment option for heat sensitive ones.
Keywords: UV-curing; direct patterning; material printing; Ultraviolet Rays; oxid křemičitý; silica binder; titania; ultrafialové záření; Silicon Dioxide; titan; Nanoparticles; Titanium; nanočástice